A stalled revolution? What can we learn from women's drop-out to part-time jobs: A comparative analysis of Germany and the UK - Martina Dieckhoff; Vanessa Gash; Antje Mertens; Laura Romeu Gordo (Research in Social Stratification and Mobility, 2016)
This study examines how within-couple inequalities, that is power differences between men and women in a partnership, act as predictors of transitions from full-time to part-time employment applying Heckman corrected probit models in three different institutional and cultural contexts; Eastern Germany, Western Germany and the United Kingdom. The analyses show that when women are in a weaker position within their relationships they are more likely to drop-out of full-time work, but that this propensity varies by context. The authors also find an increased tendency over time for women to leave full-time for part-time employment in both Eastern and Western Germany, but observe no such trend in the UK. This is suggestive of ongoing incompatibilities in the institutional support for equality in dual-earning in Germany. The study uses longitudinal data covering the period 1992 until 2012 from the German Socio-Economic Panel (SOEP) for Germany and from the British Household Panel (BHPS) and the `Understanding Society' data for the UK.
Additional information: Akzeptierte Manuskriptfassung (postprint) / Accepted version (postprint)
Keywords: 330; Part-time employment; Family; Wages; Housework; Cross-national comparison